Wind characteristics and outdoor thermal comfort assessment in east Malaysia - Hanipah, M. H.; Abdullah, A. H.; Che Sidek, N. A.; Yunus, R.; Nagapan, S.; Yassin, M. N.; Muhammad Yazid, M. N. A. W. (Universiti Putra Malaysia Press., 2017)
Rapid urbanisation and industrialisation have had an adverse and deep impact on the environment contributing to global warming and climate change. These thermal environmental problems can be even more challenging to people living in regions with warm and humid climatic conditions throughout the year, such as Malaysia. This paper analyses wind characteristics and outdoor thermal comfort index at the hottest temperatures based on data recorded hourly between 2012 and 2014 for two cities in East Malaysia, namely Kuching (Sarawak) and Kota Kinabalu (Sabah). Wind characteristics were analysed using only wind velocity and direction, while the level of outdoor thermal comfort was measured using Universal Thermal Climate Index (UTCI). The results showed that hourly average wind velocities for Kuching and Kota Kinabalu were 1.84 m/s and 2.15 m/s respectively while the highest average wind velocities was 10.1 m/s and 12.4 m/s respectively. No wind movement (i.e. 0 m/s) was recorded for both locations. The prevailing annual wind flow is generally from South-Southeast (150°) in Sarawak and from East-Southeast (110°) in Sabah. It was also found that both Kuching and Kota Kinabalu experienced strong and extreme heat stress conditions with UTCI levels of 44.8°C and 49.8°C respectively. Thus, it can be concluded that, East Malaysia faces strong and extreme heat stress conditions. This study is an original contribution on the subject of outdoor thermal environment in Malaysia, Further research to better understand outdoor thermal environmental problems is recommended.